WR 2020
DOI: 10.37763/wr.1336-4561/65.1.087100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Weathering on Surface Characteristics of Scots Pine Impregnated With Wolmanit Cx-8 and Varnished

Abstract: In this study, it was aimed to investigate the effects of weathering on some surface characteristics such as color and surface roughness changes of Scots pine impregnated with copper-containing chemical such as Wolmanit CX-8 (WCX-8) and varnished with synthetic varnish (SV), cellulosic varnish (CV), and polyurethane varnish (PV) were investigated. Results showed that while the WCX-8 impregnated and PV coated Scots pine specimens showed better color stability than other treatment groups after weathering, only C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Zhang et al [11] in their study, found that by impregnating with copper ethanolamine after the accelerated weather conditions test, they greatly prevented the change in the surface properties of the wood materials. Altay et al [12] investigated color changes of Scots pine wood impregnated with copper content chemical before synthetic, cellulosic, polyurethane varnishes (PV) coating after weathering. They found that a good color stability in the Scots pine specimens treated with Wolmanit CX-8 (WCX-8) before PV coated of weathering conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11] in their study, found that by impregnating with copper ethanolamine after the accelerated weather conditions test, they greatly prevented the change in the surface properties of the wood materials. Altay et al [12] investigated color changes of Scots pine wood impregnated with copper content chemical before synthetic, cellulosic, polyurethane varnishes (PV) coating after weathering. They found that a good color stability in the Scots pine specimens treated with Wolmanit CX-8 (WCX-8) before PV coated of weathering conditions.…”
Section: Introductionmentioning
confidence: 99%